Studies on the Sogdian epistolary tradition - Benkato, Adam (Berliner Turfantexte, 2018)
Edition of Sogdian epistolary fragments discovered in Turfan as well as a wide-ranging comparative analysis of Sogdian epistolary formulae. An important part of the Sogdian corpora which have come down to us are epistolary texts: both the earliest substantial Sogdian documents (the 'Ancient Letters') and the only substantial textual corpus found in Sogdiana itself (the Mugh documents). The Turfan collections of (especially) Berlin, Kyoto, and St. Petersburg, also preserve a number of letter fragments. Altogether, these texts attest different phases of a Sogdian epistographical tradition stretching over some seven centuries. The edition and analysis of both well-preserved and fragmentary texts can contribute to efforts to reconstruct parts of those traditions - and eventually connect them with those of Central Asia and Iran more broadly.